Analysis of slow de-trapping phenomena after a positive gate bias on AlGaN/GaN MIS-HEMTs with in-situ Si3N4/Al2O3 bilayer gate dielectrics. (January 2015) - Wu, Tian-Li; Marcon, Denis; Ronchi, Nicolo; Bakeroot, Benoit; You, Shuzhen; Stoffels, Steve; Van Hove, Marleen; Bisi, Davide; Meneghini, Matteo; Groeseneken, Guido; Decoutere, Stefaan
Highlights: We analyzed slow de-trapping phenomena in AlGaN/GaN MIS-HEMTs. A trap with activation energy of 0.69–0.7 eV was identified for the V TH shift. This trap is located at the interface between the dielectrics and AlGaN barrier. The dynamics of the traps at the interface was proposed to explain the V TH shift. Abstract: We focus on slow de-trapping phenomena in AlGaN/GaN MIS-HEMTs with a bilayer dielectric ( in-situ Si3 N4 /Al2 O3 ) with two different thicknesses of in-situ Si3 N4 (10 nm and 5 nm). By using a "filling pulse" at a positive gate voltage, a trap with activation energy of 0.69–0.7 eV was identified to be responsible for the V TH shift. Based on literature, filling conditions, and the simulated band diagrams, this trap is most probably located at the interface between the dielectrics and AlGaN barrier. A physical model is proposed to explain the V TH shift due to the trapping/de-trapping phenomena based on the occupation dynamics of donor traps at the interface between the in-situ Si3 N4 /Al2 O3 and the AlGaN barrier.